Health system analysis: Pakistan and Afghanistan - Qarani, Wais Mohammad; Iqbal Kanji, Samina (International Journal of Endorsing Health Science Research, 2015)
The purpose of this paper is to analyze the health system of the two neighboring countries i.e. Pakistan and Afghanistan; and recommend strategies to translate the available opportunities into effective actions within the countries. Therefore, the WHO, Health System Framework is used to analyze the Pakistan and Afghanistan health system in terms of; 1) leadership and governance 2) health financing 3) health workforce 4) medical products and technologies 5) information and research and 6) service delivery. Both the countries are having multiple strengths and opportunities in terms of healthcare delivery system. On the other hand, both the countries are affected by multiple challenges including; un-met Millennium Development Goals and un-met national health indicators. Thus, appropriate strategies are required to be developed and executed in order to meet the national need for health.